PENERAPAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENCIPTAKAN IKLIM SEKOLAH YANG KONDUSIF - Muthmainnah, Mutiah; Rismayanti, Rismayanti; Rosdiana, Rosdiana; Fitriani, Fitriani (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2022)
The creation of a conducive school climate is believed to be closely related to the leadership of the principal. One of them is transformational leadership, but there are things that make the application of the principal's transformational leadership style at SMPN 2 Barebbo not maximized, namely because there is still a lack of direct communication given by the principal to the teacher so that the teacher feels that there is a lack of attention from the principal. The purpose of this research is to find out the form of implementing transformational leadership of the principal and find out the solutions that hinder the creation of a conducive school climate at SMPN 2 Barebbo by interviewing the principal and vice principal of public relations as well as student affairs. the method used in this research is a field research method with a qualitative approach aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually and in groups. while the results of this study indicate that the principal in overcoming the inhibiting factors for the creation of a conducive school climate by implementing transformational leadership at SMPN 2 Barebbo has been going well, this can be seen from how the principal tries and seeks to improve the quality of the school following the times with ideas which is able to motivate and grow the spirit of the school community and invites the school community to intervene and participate optimally in terms of developing school quality.